Des régulations en lien avec l’âge, la santé et les caractéristiques du travail : le cas des infirmières d’un centre hospitalier français - Olivier Gonon (Perspectives Interdisciplinaires sur le Travail et la Santé)
In a context marked by an aging of the nursing population in France, this paper proposes a framework for regulations concerning age, health and working conditions. Three kinds of regulation are defined, namely organizational (turnover within the hospital), collective (new task allocation within the team) and individual (changing working methods). The results of different studies (epidemiology, work demography, professional course analyses, interviews, questionnaires and work analysis) show that the professional careers of nurses are influenced by shift-work and physical or emotional constraints. In « young » units, several types of reciprocal assistance and task re-allocation between nurses were observed to help the nurses deal with these constraints. Individual regulation depends on the flexibility available to those concerned ; the more severe the work constraints, the more difficulties the nurses face in applying their skills. In conclusion, the authors propose that future consideration should focus on the simultaneous implementation of the three types of regulation.